AMA0428, A Potent Rock Inhibitor, Attenuates Early and Late Experimental Diabetic Retinopathy. (1st February 2017) - Hollanders, Karolien; Hove, Inge Van; Sergeys, Jurgen; Bergen, Tine Van; Lefevere, Evy; Kindt, Nele; Castermans, Karolien; Vandewalle, Evelien; van Pelt, Jos; Moons, Lieve; Stalmans, Ingeborg
ABSTRACT: Purpose : Diabetic retinopathy (DR) is characterized by an early stage of inflammation and vessel leakage, and an advanced vasoproliferative stage. Also, neurodegeneration might play an important role in disease pathogenesis. The aim of this study was to investigate the effect of the Rho kinase (ROCK) inhibitor, AMA0428, on these processes. Methods : The response to ROCK inhibition by AMA0428 (1 µg) was studied in vivo using the murine model for streptozotocin (STZ)-induced diabetes, focusing on early non-proliferative DR features and the oxygen-induced retinopathy (OIR) model to investigate proliferative DR. Intravitreal (IVT) administration of AMA0428 was compared with murine anti-VEGF-R2 antibody (DC101, 6.2 µg) and placebo (H2 O/PEG; 1C8). Outcome was assessed by analyzing leukostasis using fluorescein isothiocyanate coupled concanavalin A (FITC-ConA) and vessel leakage (bovine serum albumin conjugated with fluorescein isothiocyanate; FITC-BSA)/neovascularization and neurodegeneration by immunohistological approaches (hematoxylin and eosin (H&E), terminal deoxynucleotidyl transferase–mediated biotinylated UTP nick end labeling (TUNEL), Brn3a). ELISA and Western blotting were employed to unravel the consequences of ROCK inhibition (1 µM AMA0428) on myosin phosphatase target protein (MYPT)-1 phosphorylation, endothelial nitric oxide synthase (eNOS) phosphorylation, and vascular endothelial growth factor (VEGF) levels in retinas of diabetic mice, on NF-κβ activity and ICAM-1 expression in endothelial cells (ECs). Results: In vivo, AMA0428 significantly reduced vessel leakage and neovascularization, respectively, in the STZ and OIR model, comparable to DC101 therapy. Additionally, the ROCK inhibitor decreased neurodegeneration in both models and inhibited leukostasis by 30% ( p < 0.05) in the STZ model ( p < 0.05), while DC101 had no positive effect on the outcome of these latter processes. ROCK activity was upregulated in the diabetic retina and AMA0428 administration resulted in decreased phospho-MYPT-1, enhanced phospho-eNOS, and reduced VEGF levels. In vitro, AMA0428 interfered with NF-κβ activity, thereby inhibiting ICAM-1 expression in ECs. Conclusions : Targeting ROCK with AMA0428 effectively attenuated outcome in an early DR model (STZ) and a late vasoproliferative retinopathy model (OIR). These findings make AMA0428 a promising candidate with an additional anti-inflammatory and neuroprotective benefit for DR patients, as compared with anti-VEGF treatment.